Squatted houses and city politics: communication and contention in Firenze - Tommaso Frangioni (Amnis)
This paper is a study on the housing policy arena in Firenze. During the last years, local city governments have been focusing on fostering international, high-profile tourism. The local SMO, Movimento Lotta per la Casa (literally, Fight for the Housing Movement) has some traits of NSMs. At the same time, there are elements that remind « old » Social Movements. It is addressing a material issue, it exercises a very physical resistance and its grammar of disobedience relies on the appropriation of urban spaces. Through the lens of the « Right to the City », I discuss here the relation between urban movements and the urban regime.